Trans-Disc Aspiration of Anterior Cervical Cysts - Ebrahim, Zahier; Gretschel, Armin; van der Horst, Alex; Vlok, Adriaan J. (Indian Journal of Neurosurgery, 2024)
Background Spinal arachnoid cysts are rare entities occurring mainly in the cervical and thoracic spine. The majority of these lesions are treated through posterior approaches with laminectomy or laminotomy. We present trans-disc and trans-vertebral aspiration of anterior cervical arachnoid cysts as an alternative therapeutic approach.Methods We present three cases and four procedures where anterior cervical arachnoid cysts were treated through an anterior trans-discal or trans-vertebral approach. A standard Smith–Robertson approach was used to expose the appropriate level in the cervical spine. A 22-gauge spinal needle is passed through the intervertebral disc or a 3-mm channel created in the midline of the vertebral body. This is performed under fluoroscopic guidance.Results Three out of the four procedures resulted in complete clinical resolution at a 6-month follow-up. One patient required a repeat aspiration for a recurrent cyst at a level lower than the previous procedure. One patient had an initial improvement post-procedure followed by a functional decline within the first 5 postoperative days. Our assessment was that the cyst was re-filled and this was confirmed on magnetic resonance imaging (MRI). A standard posterior approach was used to excise the cyst with a good clinical result. Overall, no morbidity was suffered from the anterior approach.Conclusion We believe this approach is a safe alternative to posterior intradural approaches. MRI scanning is advised at 6 months or earlier if clinical improvement is not demonstrated.
Keywords: cervical; arachnoid cysts; trans-disc